2021
DOI: 10.1126/scitranslmed.abg9890
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation using ultra low frequency current waveform reversibly blocks axonal conduction and chronic pain

Abstract: Chronic pain remains a leading cause of disability worldwide, and there is still a clinical reliance on opioids despite the medical side effects associated with their use and societal impacts associated with their abuse. An alternative approach is the use of electrical neuromodulation to produce analgesia. Direct current can block action potential propagation but leads to tissue damage if maintained. We have developed a form of ultra low frequency (ULF) biphasic current and studied its effects. In anesthetized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
5
15
1
Order By: Relevance
“…Subject 3 also reported that PLP increased when testing was paused for a week. The recurrence of PLP aligns with anecdotal evidence from traditional SCS studies which report that the wash-in and wash-out period of SCS can be 3-7 days 35 . Our observations build on growing evidence that somatosensory neuroprosthetic systems are associated with a decrease in PLP 7,[11][12][13][14] .…”
Section: Discussionsupporting
confidence: 77%
“…Subject 3 also reported that PLP increased when testing was paused for a week. The recurrence of PLP aligns with anecdotal evidence from traditional SCS studies which report that the wash-in and wash-out period of SCS can be 3-7 days 35 . Our observations build on growing evidence that somatosensory neuroprosthetic systems are associated with a decrease in PLP 7,[11][12][13][14] .…”
Section: Discussionsupporting
confidence: 77%
“…This could potentially cause a greater change in the BOLD signal activity being measured in the ROIs after TUS, which causes a greater loss of activity coupling between the ACC and these regions. Such observation feeds directly into the wider discussion of the use of neuromodulation for pain management, where a current is understood to block the signal in a similar fashion [72,73].…”
Section: Discussionmentioning
confidence: 89%
“…Behavior and electrophysiological evidence have demonstrated that activation of low-threshold mechanoreceptors could alleviate pain symptoms and inhibit the spontaneous discharges of dorsal horn neurons. [39][40][41][42] This analgesic effect has been generally explained by the gate control theory, which suggests that the nociceptive (Aδ/C) inputs are gated by feed-forward activation of non-nociceptive (Aβ) afferents in SDH. The spinal WDR neurons receive inputs from both non-nociceptive (Aβ) and noxious (Aδ and C) afferents.…”
Section: Discussionmentioning
confidence: 97%